Nursing management of treatment-related venous thromboembolism in patients with multiple myeloma - Yang, Bianhong; Liu, Chao; Lin, Zeyu; Geng, Chuanying; Zhang, Zhiyao (Frontiers in Medicine, 2023)
Objectives Venous thromboembolism (VTE) is a common complication among patients with newly diagnosed multiple myeloma (NDMM). Therefore, this study aimed to analyze the incidence and risk factors associated with VTE in the current era of thromboprophylaxis and to propose appropriate nursing measures. Methods A total of 1,539 NDMM patients were retrospectively analyzed. All patients underwent VTE risk assessment and received aspirin or low molecular weight heparin (LMWH) to prevent thrombosis, followed by appropriate care based on their individual thrombosis risk. The incidence of VTE and its related risk factors were then analyzed. Results All patients received at least four cycles of therapy containing immunomodulators (IMiDs) and/or proteasome inhibitors (PIs). We assigned 371 patients (24.1%) to the moderate-risk thrombosis group, who received daily aspirin (75 mg) for thrombosis prevention and 1,168 patients (75.9%) to the high-risk group, who received daily low molecular weight heparin (3,000 IU) for thrombosis prevention two times a day. Among all the patients, 53 (3.4%) experienced lower extremity venous thromboembolism events, with three of those patients experiencing a concurrent pulmonary embolism. A multivariate analysis indicated that bed rest lasting more than 2 months and plasma cells of ≥60% were independent factors associated with thrombosis. Conclusion More effective risk assessment models are needed to predict thrombosis accurately. In addition, nurses involved in the treatment and management of thrombosis should continually engage in professional development to enhance their knowledge and skills.